It's safe and healthy! Increasing consumers' willingness to consume aging produce. (October 2022) - Neubig, Christina M.; Roosen, Jutta; Karg, Cornelia A.; Moser, Simone
Highlights: This study investigates how to increase consumption of aging produce. Informing consumers about safety and healthfulness increases willingness to consume. Safety and health perception predict willingness to consume aging produce. Being easily disgusted and relying on expiration dates reduce willingness to consume. Consumers who prefer vegetarian dishes are more willing to consume aging produce. Abstract: Consumers' tendency to waste suboptimal food poses challenges for sustainable food systems. In the case of aging produce, consumers often experience a conflict between the goals of not wanting to waste food and food safety. In addition to safety, perceived healthfulness can influence the decision between consumption and disposal of (suboptimal) food items. Using an online information experiment on the safety and healthfulness of aging produce, this study investigates consumers' willingness to consume aging produce. Results show that providing information on safety or healthfulness results in increased safety and health perception, which in turn increases willingness to consume aging produce. In addition, consumers with lower food disgust sensitivity, a decision style characterized by less reliance on expiration dates, and a preference for vegetarian dishes are more willing to consume aging produce. This study adds to the growing body of literature discussing how to increase the consumption of suboptimal foods. The results imply that informing consumers about safety and healthfulness can be a viable path to increase the consumption of aging produce at home.